Mindfulness and flow in elite athletes - Cathcart, S.; McGregor, M.; Groundwater, E. (Journal of Clinical Sport Psychology, 2014)
Mindfulness has been found to be related to improved athletic performance and propensity to achieve flow states. The relationship between mindfulness and flow has only recently been examined in elite athletes. To build on this literature, we administered the Five-Facet Mindfulness Questionnaire (FFMQ) and the Dispositional Flow Scale to 92 elite athletes. Psychometric analyses supported the validity of the FFMQ. Males scored higher than females on the FFMQ facet of Nonjudging of Inner Experience. Athletes from individual and pacing sports scored higher on the FFMQ facet of Observing than athletes from team-based and nonpacing sports. Correlations between mindfulness and flow were stronger in athletes from individual and pacing sports compared with team-based and nonpacing sports. Mindfulness correlated with different facets of flow in males compared with females. The results support the use of the five-facet mindfulness construct in elite athletes and suggest the relationship between mindfulness and flow possibly may vary by gender and sport type in this population.